Harm reduction strategies for androgen users: providing appropriate support and improving engagement with healthcare. Issue 6 (15th December 2021) - Bates, Geoff; Shepherd, Scott; McVeigh, Jim
Abstract : Purpose of review: As evidence continues to emerge of the harms associated with nonmedical androgen use, this review explores the implications from recent studies for designing strategies to reduce harm and support good health amongst androgen users. Recent findings: Studies have predominantly come from researchers in the UK and Australia. Major themes include questioning the scope and content of harm reduction strategies and identifying approaches to improve engagement between the androgen using community and healthcare providers. Findings suggest that a broader range of interventions and forms of advice are needed than are commonly provided. This must be supported by efforts to increase opportunities to deliver harm reduction through new engagement approaches, better relationships with health professionals and more guidance on identifying and managing associated adverse health impacts. Summary: A fully developed harm reduction-based response to nonmedical androgen use will be one that not only seeks to reduce risk of bloodborne virus transmission and injecting-related harms, but that considers the range of needs amongst the diverse community of androgen users and respects their decisions and rights. Co-producing interventions with members of this community will help develop effective and engaging approaches. Rigorous studies are needed to evaluate new harm reduction interventions as well as those already delivered.